Associations of the levels of adipokines and cytokines in individual follicles with in vitro fertilization outcomes in women with different ovarian reserves - Xuelan Li; Chujun Li; Jie Yang; Min Lin; Xianli Zhou; Ziyang Su; Yuting Zhang; Xinning Li; Xin Chen (Journal of Ovarian Research)
Abstract Background To a large extent, the ovarian reserve determines a woman’s reproductive potential. The etiological and pathological mechanisms of diminished ovarian reserve (DOR) remain unclear, and no reliable treatment is currently available for DOR. Adipokines and cytokines in follicular fluid (FF) play pivotal roles in follicular development and maturation. The concentrations of adipokines and cytokines in FF from individual follicles of women with DOR undergoing in vitro fertilization (IVF) were studied. In particular, we investigated the associations between the levels of adipokines and cytokines in individual FFs from women with different ovarian reserves and between the follicular levels of adipokines and cytokines and IVF outcomes in individual follicles. Methods A total of 115 women who underwent IVF were recruited. Patients diagnosed with DOR, defined as a basal antral follicle count < 5 or an anti-Mullerian hormone concentration < 1.1 ng/mL, were assigned to the DOR group, while patients with a normal ovarian reserve (NOR) were assigned to the NOR group. FF was sampled from the first follicle with a diameter of approximately 18–20 mm from each patient, and the IVF outcome of the oocyte from the corresponding follicle was tracked. The levels of 5 adipokines (including visfatin-1, monocyte chemoattractant protein-1 [MCP-1], resistin, leptin, and chemerin) and 3 cytokines (including interleukin [IL]-6, IL-12p70, and tumor necrosis factor [TNF]-α) in FF were determined by Luminex technology. Results The follicular levels of TNF-α, IL-6, visafatin, MCP-1, IL-12, and chemerin were significantly lower in women with NOR than in those with DOR. The follicular level of IL-6 was negatively correlated with the quality of embryos according to the binary logistic regression analysis, while the follicular levels of adipokines and other cytokines did not correlate with IVF outcomes regardless of the woman’s ovarian reserve. Conclusions Our study demonstrated that the levels of adipokines and cytokines in individual follicles in women with DOR were different from those in women with NOR, indicating that increased intrafollicular inflammation might be related to DOR. Moreover, a high follicular level of IL-6 might negatively impact embryo quality.